1983
DOI: 10.1073/pnas.80.15.4732
|View full text |Cite
|
Sign up to set email alerts
|

Increased membrane permeability to chloride in Duchenne muscular dystrophy fibroblasts and its relationship to muscle function.

Abstract: Previous studies have suggested an abnormality in Cl-metabolism in Duchenne muscular dystrophy (DMD) fibroblasts. In order to further characterize this abnormality, we have studied mCl-distribution and permeability in 11 DMD and 12 normal fibroblast lines. Under steady-state conditions Cl-efflux in fibroblasts is observed to be biphasic, revealing the presence of two major subcellular compartments. Each compartment contains approximately half of the cellular C1-. The faster of the two observed efflux component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…These enzymes may act primarily as dipeptidases, with a very restricted capacity for the degradation of naturally occurring oligopeptides. With the exception of the greater increase in activity in the presence of 0.15 M C1-and Br-anions, which we have observed with I and 11, the characteristics of these enzymes appear to correspond reasonably closely with those of the so-called aminopeptidase B previously described in other species and/or tissues 12, 7, 81. This paper describes the purification and characterization of two C1--activated aminopeptidases hydrolysing basic termini from human skeletal muscle, as part of a systematic investigation of the role of aminopeptidases in the protein turnover of normal and diseased muscle; it is of interest that Pato et al [9] have recently suggested that there is an increased permeability of the muscle membrane to C1-anions in muscular dystrophy. Table 5.…”
Section: Enzyme Activity On Peptide Substratesmentioning
confidence: 99%
“…These enzymes may act primarily as dipeptidases, with a very restricted capacity for the degradation of naturally occurring oligopeptides. With the exception of the greater increase in activity in the presence of 0.15 M C1-and Br-anions, which we have observed with I and 11, the characteristics of these enzymes appear to correspond reasonably closely with those of the so-called aminopeptidase B previously described in other species and/or tissues 12, 7, 81. This paper describes the purification and characterization of two C1--activated aminopeptidases hydrolysing basic termini from human skeletal muscle, as part of a systematic investigation of the role of aminopeptidases in the protein turnover of normal and diseased muscle; it is of interest that Pato et al [9] have recently suggested that there is an increased permeability of the muscle membrane to C1-anions in muscular dystrophy. Table 5.…”
Section: Enzyme Activity On Peptide Substratesmentioning
confidence: 99%
“…1; for each pair of cell cultures the number of experiments is given in parentheses. Data were analyzed assuming two parallel cellular compartments from which efflux occurred by first-order kinetics (7,9 this day-to-day variation, in any single experiment CF and N fibroblasts had comparable 3-O-MeGlc contents, corresponding to mean values of 4.96 and 5.20 jl/mg of protein. Therefore, because cell volume does not differ between CF and control fibroblasts, the lowered 36CL-capacity of CF cells corresponded to a lowered overall Cl-concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Such kinetic analysis cannot identify the biological equivalents of compartments A and B without further work, nor can one assume that compartments identified by studies of 36CL-efflux correspond to the compartments (A' and B') found by analysis of 22Na+ efflux. Nevertheless, it is customary to assume that the more rapidly emptying compartment represents cytosol and that more slowly turning-over compartments reflect one or more subcellular organelle(s) or perhaps bound material (7,9,10). In this regard, it should be noted that the values derived in this analysis describe isotope efflux from parallel and independent compartments, and for simplicity we have tabulated the data in this way.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations